2010
DOI: 10.1073/pnas.1006886108
|View full text |Cite
|
Sign up to set email alerts
|

Protease activated receptor-1 inhibits the Maspin tumor-suppressor gene to determine the melanoma metastatic phenotype

Abstract: The thrombin receptor protease activated receptor-1 (PAR-1) is overexpressed in metastatic melanoma cell lines and tumor specimens. Previously, we demonstrated a significant reduction in tumor growth and experimental lung metastasis after PAR-1 silencing via systemic delivery of siRNA encapsulated into nanoliposomes. Gene expression profiling identified a 40-fold increase in expression of Maspin in PAR-1-silenced metastatic melanoma cell lines. Maspin promoter activity was significantly increased after PAR-1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…The thrombin receptor, protease-activated receptor-1, which is overexpressed in metastatic melanoma cell lines and tumor specimens, plays a key role in serving this function during melanoma progression. Recently, pro- tease-activated receptor-1 has been reported to regulate the gap junction protein connexin 43 and the tumor suppressor gene maspin to promote the metastatic melanoma phenotype [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…The thrombin receptor, protease-activated receptor-1, which is overexpressed in metastatic melanoma cell lines and tumor specimens, plays a key role in serving this function during melanoma progression. Recently, pro- tease-activated receptor-1 has been reported to regulate the gap junction protein connexin 43 and the tumor suppressor gene maspin to promote the metastatic melanoma phenotype [26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic melanoma cells were recently found to have lower levels of maspin expression, compared to normal human epidermal melanocytes. We recently demonstrated that in two highly metastatic melanoma cell lines, PAR-1 inhibits maspin expression by promoting the phophorylation of p38, decreasing the recruitment of CBP/p300, as well as c-Jun and Ets-1 transcription factors, to the maspin promoter (13). This inhibition results in increased melanoma cell invasion.…”
Section: The Effect Of Thrombin/par-1 On Tumor Cellsmentioning
confidence: 99%
“…For instance, its proteolytic activation by thrombin caused persistent activation of EGFR/ERK signaling, promoting thereafter breast carcinoma cell invasion [54] . Moreover, PAR-1 negatively regulated the expression of the Maspin tumor-suppressor gene contributing to the metastatic phenotype of melanoma [55] . It has been recently reported that metalloprotease-1 (MMP1) may function as a protease agonist of PAR-1 which then stimulates migration, invasion and angiogenesis in breast and ovarian malignancies [56,57] .…”
Section: Gpcrs Activated By Peptidesmentioning
confidence: 99%